(untitled) (Journal of the College of Basic Education, 2023)
Astronomy was one of the most closely related sciences to the Islamic cultural and social reality. Rather, it gained a certain specificity thanks to its treatment of religious issues of concern to Muslims anywhere at that historical stage. We find that determining the direction of the Qiblah (Makkah Al-Mukarramah) from several different points on the surface of the earth and the classification of astronomical tables For the timing of prayer with all these local issues